Seasonal variations in the abundance and body size distribution of the ocean sunfish Mola mola in coastal waters off southern Portugal. (27th December 2018) - Baptista, Miguel; Couto, Ana; Paula, José Ricardo; Raimundo, Joana; Queiroz, Nuno; Rosa, Rui
Abstract: The present work expands the existing knowledge on M. mola ecology by assessing, for the first time, its abundance (and body size distribution) in the southern waters of Portugal and relating the associated temporal variations with environmental variables. There were significant seasonal differences in abundance, with peaks in spring and autumn and lower values throughout the summer. Ocean sunfish abundance was positively correlated with sea surface temperature and chlorophyll a, indicating that a combination of both temperature and productivity dictates spatial use. Complementarily, the absence of a relationship between abundance and water transparency may reveal a strategy in spatial use favouring a medium-term steady food supply over short-term improved feeding opportunities. Specimens ranged between 31.8 and 230.0 cm (total length), with 98% of all individuals measuring between 31.8 and 59.9 cm. As the vast majority of specimens analysed were immature, seasonal differences in abundance should not be related to spawning.